O financiamento da educação básica pública em Mato Grosso por meio do Salário-Educação - Bartolomeu José Ribeiro de Sousa (2019)
This report presents the preliminary results of the research "The Financing of Public Basic Education in Mato Grosso through the Salary-Education." The research had the object of research the Salary-Education, defined in the legislation as an additional source of financing of public basic education . The general objective of the research was to analyze the public resources management of the Municipal Salary of Education Salaries in the State of Mato Grosso, the public expenditure process and the external control carried out by the Court of Accounts of the State of Mato Grosso (TCE-MT). With the use of the qualitative and quantitative approach, the research aimed at articulating in its investigative scope the management of the resources of the Municipal Salary-Education quotas, with the external control carried out by the Court of Accounts of Mato Grosso. In order to understand the Salary-Education in the financing of public basic education, its institutional trajectory, changes in the normative base and its importance, a theoreticalmethodological construct denominated normative physiology has been developed that involves the central questions related to the operation of the contribution. The documentary research corpus comprised a broad base of documents that included all legislation on Salary Education and official documents, municipal budget laws, accounting statements of expenses and the Prior Opinion on the government accounts of the municipalities of the sample. The analyzed data show the main results: at the planning stage, a prevailing invisibility of the Education Salary in the budget laws, which weakens the planning process; in the execution of resources, there is a tendency in which they are used for the most diverse types of costing expenditures, which deviates from its constitutional purpose as an additional and additional source of financial resources for basic education and, in As regards external control, the TCE-MT did not deliberate specifically on procedures for the use of resources of the Education Salary by the municipalities, which imposes limits on accountability and social control